Analisis Kebijakan UU Nomor 1 Tahun 2024 (untuk Penanganan Cyber Bullying) dengan Perspektif Problem Tree Analysis - Ira Febriana; Shifa Intan Rahma (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Acts of cyberbullying are increasingly common in Indonesia. Whatsapp, Instagram and Facebook were identified as the top three social media platforms used by perpetrators to commit cyberbullying. Law Number 1 Year 2024 on Electronic Information and Transactions (ITE Law) provides the legal basis for addressing cyberbullying in Indonesia. Although the ITE Law provides a strong legal basis for dealing with cyberbullying, there are still challenges in its implementation. The method used in this research is a literature study by tracing various literature related to the analysis of the ITE Law, and handling cyberbullying. In addition, the author also analyzes the problem using the problem tree analysis method. In this study, it was found that the ITE Law has provided a clear legal framework for handling cyberbullying, but in its implementation it still faces several obstacles, such as the legal process is often slow and bureaucratic, there is a misalignment between central and regional regulations, and people who do not understand the provisions of the ITE Law and how to report cyberbullying cases. So that in handling cyberbullying, the active role of various parties is still needed, including the government, educational institutions, families, and digital platforms.